Released Parasite-Derived Kinases as Novel Targets for Antiparasitic Therapies - Silvestre, Anne; Shintre, Sharvani Shrinivas; Rachidi, Najma (Frontiers in Cellular and Infection Microbiology, 2022)
The efficient manipulation of their host cell is an essential feature of intracellular parasites. Most molecular mechanisms governing the subversion of host cell by protozoan parasites involve the release of parasite-derived molecules into the host cell cytoplasm and direct interaction with host proteins. Among these released proteins, kinases are particularly important as they govern the subversion of important host pathways, such as signalling or metabolic pathways. These enzymes, which catalyse the transfer of a phosphate group from ATP onto serine, threonine, tyrosine or histidine residues to covalently modify proteins, are involved in numerous essential biological processes such as cell cycle or transport. Although little is known about the role of most of the released parasite-derived kinases in the host cell, they are examples of kinases hijacking host cellular pathways such as signal transduction or apoptosis, which are essential for immune response evasion as well as parasite survival and development. Here we present the current knowledge on released protozoan kinases and their involvement in host-pathogen interactions. We also highlight the knowledge gaps remaining before considering those kinases - involved in host signalling subversion - as antiparasitic drug targets.